APLIKASI SEMIOTIKA NARATIF A. J. GREIMAS TERHADAP KISAH THALUT DALAM AL-QUR’AN - Nor Istiqomah (Institut Agama Islam Negeri (IAIN) Keiri, 2017)
This paper aimed to explore the interpretation of the story of Thalut in QS. al-Baqarah: 246-251 using the semi-narrative theory of A.J. Greimas as an analytical tool. This structural theory is expected to explore the structure text of the text of the Qur’an. In addition, the narrative semiotics theory also opens up a new understanding of the text by looking at the inner structure and inner structure of the text. This understanding is not new, but it is able to bring meaning that is slightly diverse than most. The findings of the authors obtain that the story of Thalut in the Qur’an at least contains two structures of the narrative meaning of the text, namely the birth and the mind. The understanding gained from the textual structure of the narrative text is the existence of segments that describe how the Thalut struggle to save people from religious, socio-political and even moral crisis with the support of prayer, belief and knowledge. However, he is hindered by his hesitant and arrogant nature. As we know from the inner structure of the text, the story of Thalut in QS. Al-Baqarah: 246-251 shows how the verse describes the spirit of a person in reaching a business which in psychology studies is known also with the phenomenon of will (conation). In addition, the author sees the existence of other elements such as cultural inheritance (cultural transfered) that occurred in the Children of Israel. With the theory of narrative semiotics, the text of the Qur’an becomes more broadly meaningful and not only fixated on textual understanding.